Diseño de una red interna de telemedicina para el Hospital Universitario de Motupe. - Espinoza Mora, José Luis (2013)
In this graduation project I have designed an internal network of telemedicine, that’s totally modern and complete in which this contributes to the improvement of the services that the “Hospital Universitario de Motupe” the National University of Loja offers, that’s oriented to the management of the medical information that’s generated, in one piece of network the infrastructure is well equipped with a variety of high technology, this contributes to improving the system for public services, through the use of Technologies of Information and Communication (TIC). To enlarge the services that the “Hospital Universitario de Motupe”offers, I will perform a technological analysis to the medical team this will be necessary for the creation of the radiology and cardiology areas; in this way we can facilitate the management of file transfer, papers and pictures in a digital format, guaranteed savings on printed radiographic films. The administration and management of the medical information (HIS-RIS-PACS) from the “Hospital Universitario Motupe” it’s a robust tool that facilitates the application of multiple systems for the administration, also a backup and some tools to transmit the information; it also enables dynamic development of integrated network facilitating in a better and fast way the electronic clinical history of the patients. For the operation of the system and for this to work well we have required a continuous connection to the internet network, for this we must use two different service providers, just in case one of them fails, the other one can maintain active without having the risk of staying totally incommunicated. In the country the policy is described in the “Plan Nacional del Buen Vivir” This proposes that all the public institutions, have to be implemented in a way that it could bring quality in the services, even though when it comes to health, this plan guarantees the comprehensive health for the town. This is the main reason that justifies the inversion which involves the implementing a design for the benefits that’s presented and those they are exposed in this piece of thesis.